Temporary gastro-electrical stimulation improves gastric emptying and quality of life in patients with refractory gastroparesis. (13th March 2011) - Gibson, S; Clark, L; Jamieson, N; Fullarton, G
Abstract : Introduction: Gastro-electrical stimulation (GES) is an accepted method of managing severe drug refractory gastroparesis. Temporary GES may help select which patients would most benefit from the permanent GES treatment; however, data on the practicality and efficacy of temporary GES are lacking. The aim of this study was to determine the efficacy of temporary GES in patients with refractory gastroparesis. Methods: Patients with confirmed drug refractory gastroparesis (t ½ > 90 m) were selected for temporary GES. Pre-procedure gastric isotope emptying data, and visual analogue symptom score were prospectively gathered. A temporary GES electrode (model 6414-200 Medtronic Ltd) was inserted endoscopically into the gastric antrum and secured with an Olympus Quickclip (Olympus Corp). Electrodes were then secured trans-nasally and connected to an external GES device (Enterra, Medtronic Ltd) set at 14 Hz frequency and standard amplitude (5–10 mA). Post-procedure gastric isotope emptying studies were repeated on day 4 and patients provided daily symptom scores on a visual analogue scale. Patients scored overall well-being on a scale of −3 (worst) to +3 (best). Nausea and vomiting were judged by patients on a scale of 0 (best) to 4 (worst). Results: Some 22 patients underwent insertion of a temporary GES electrode with no associated morbidity. Median patient age was 41 (17–62). 17 of the 22 cases of gastroparesis were idiopathic in nature, 3 were post-surgical and 2 were diabetic. Gastric isotope emptying time (t ½) improved in 16/22 patients (73%). The median (interquartile range) pre-operative gastric isotope emptying time (t ½) (minutes) was 251 (139.5–388.5) versus 100.5 (45.5–137) post-operatively (p = 0.005). The overall score of well-being improved in 18/19 patients (95%). The median pre-procedure score was −3 versus 2 post-procedure (p < 0.001). Symptoms of vomiting improved in 14 of 19 patients (74%). Median vomiting score was 3 pre-operatively versus 0 post-operatively (p < 0.001). Symptoms of nausea improved in all 18 patients completing this aspect of the questionnaire with the median score pre-procedure 3 versus 0.5 post-procedure (p < 0.001). Symptoms of pain, early satiety and bloating also demonstrated improvement post procedure. Conclusion: Temporary GES improves gastric emptying, symptoms and perception of well-being in patients with refractory gastroparesis. The longer-term outcome of permanent GES in these patients is yet to be confirmed.